Aplikasi Teknologi Pengolahan dan Pengemasan Teh Jeruju di Desa Bintunan Kecamatan Batik Nau Kabupaten Bengkulu Utara - Andari, Mayang; Wati, Fesy Hendria; Boy, Dias; Nur'aini, Hesti; Afriani, Ririn (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The aim of this community service activity is to provide knowledge to the community concentrated on PKK women regarding knowledge and technology in the field of processing and packaging technology with the hope of providing inspiration for the community to run their own businesses and increase household income. The approach method used by the proposer and partners is to determine a vision and mission that can be a solution to partner problems, including through socialization by synergizing activities based on the use of existing resources. Partners in this activity are PKK women from Bintunan Village, Batiknau District, North Bengkulu Regency. So far, jeruju leaves are often found around the environment and have not been utilized optimally. Product marketing is carried out using social media assisted by assistance. The results of receiving the benefits of this service can also be seen from the enthusiasm of the socialization participants and village officials in receiving information and applying processing, packaging and labeling technology.